2018
DOI: 10.26633/rpsp.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Why individuals fail to collect HIV-test results: an exploratory study at a testing and counseling center in Mexico City

Abstract: Objective To identify the characteristics of clients at an HIV clinic in Mexico City who fail to collect their HIV test results and to explore the reasons for non-collection. Methods This was an exploratory, cross-sectional study that used 2016 program data from the HIV Testing and Counseling Center in Mexico City. Clients with a negative HIV-test result in 2016 were classified as collectors or non-collectors, and their sociodemographic and behavioral characteristics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies among MSM in other countries found that 5–11% of MSM had failure-to-return for HIV test results [ 19 , 22 ]. Prior literature reveals significant correlates of failure-to-return for HIV test results, including perceived risk of HIV infection, inconsistent condom use, and certain demographic characteristics such as male gender, young age, unemployment, rural residence, and low educational attainment [ 19 , 23 , 24 , 25 , 26 ]. Although these studies provide salient insights into factors associated with failure-to-return for HIV test results, few studies assessed relevant psychosocial determinants and their effects on HIV prevention uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Studies among MSM in other countries found that 5–11% of MSM had failure-to-return for HIV test results [ 19 , 22 ]. Prior literature reveals significant correlates of failure-to-return for HIV test results, including perceived risk of HIV infection, inconsistent condom use, and certain demographic characteristics such as male gender, young age, unemployment, rural residence, and low educational attainment [ 19 , 23 , 24 , 25 , 26 ]. Although these studies provide salient insights into factors associated with failure-to-return for HIV test results, few studies assessed relevant psychosocial determinants and their effects on HIV prevention uptake.…”
Section: Introductionmentioning
confidence: 99%